Epidermal growth factor receptor mutations and brain metastases in non-small cell lung cancer - Zhao, Wei; Zhou, Wei; Rong, Li; Sun, Mao; Lin, Xing; Wang, Lulu; Wang, Shiqiang; Wang, Ying; Hui, Zhouguang (Frontiers in Oncology, 2022)
Studies have revealed that non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutations has a high incidence of brain metastases (BMs). However, the association between EGFR mutations and BMs remains unknown. This review summarizes detailed information about the incidence of BMs, clinical and imaging characteristics of BMs, brain surveillance strategies, influence of treatments on BMs, prognosis after BMs, and differences in EGFR mutations between paired primary tumors and BMs in EGFR-mutated NSCLC. The prognostic results demonstrate that patients with mutated EGFR have a higher incidence of BMs, EGFR-TKIs (afatinib and osimertinib) delay the development of BMs, and patients with mutated EGFR with synchronous or early BMs have a better overall survival after BMs than those with wild-type EGFR. The EGFR mutation status of BM sites is not always in accordance with the primary tumors, which indicates that there is heterogeneity in EGFR gene status between paired primary tumors and BMs. However, the EGFR gene status of the primary site can largely represent that of BM sites. Among patients developing synchronous BMs, patients with mutated EGFR are less likely to have CNS symptoms than patients with wild-type EGFR. However, the possibility of neuro-symptoms is high in patients with metachronous BMs. Patients with mutated EGFR trend to have multiple BMs compared to that of patients with wild-type EGFR. Regarding very early-stage NSCLC patients without neuro-symptoms , regular follow-up of neuroimaging is not recommended. Among advanced NSCLC patients with EGFR mutation, liberal follow-up of brain imaging at first several years showed more advantages in term of cost.